Assessing the Challenges and Opportunities of Collaborative Governance in Multi-Stakeholder Policy Environments - Kader, Abdurrahman; Fahri, Ririn (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2025)
This article explores the challenges and opportunities associated with collaborative governance in multi-stakeholder policy environments. Utilizing a qualitative approach, we conducted a comprehensive literature review to identify key themes and insights regarding collaborative governance practices. The findings reveal that while collaborative governance offers significant potential for enhancing stakeholder engagement and fostering innovative solutions to complex policy issues, it also presents notable challenges. These challenges include power imbalances among stakeholders, difficulties in communication and coordination, and the risk of diluted accountability. Conversely, the opportunities identified include the potential for shared knowledge creation, increased resource mobilization, and improved policy outcomes through collective decision-making. By synthesizing existing research, this study provides a nuanced understanding of the dynamics at play in collaborative governance frameworks and emphasizes the importance of fostering inclusive participation and effective communication strategies. The insights gained from this study can inform policymakers and practitioners seeking to enhance collaborative governance efforts in various sectors. Ultimately, this article contributes to the growing body of literature on collaborative governance by highlighting the intricate balance between challenges and opportunities, thereby offering practical recommendations for improving multi-stakeholder collaboration in policy environments